Gas-poor Hosts and Gas-rich Companions of z ≈ 3.5 Radio Active Galactic Nuclei: ALMA Insights into Jet Triggering and Feedback - Wuji Wang; Carlos De Breuck; Dominika Wylezalek; Matthew D. Lehnert; Andreas L. Faisst; Andrey Vayner; Nicole Nesvadba; Joël Vernet; Pranav Kukreti; Daniel Stern (The Astrophysical Journal Letters)
Cold gaseous systems play important roles in galaxy evolution by possibly providing fuel to ignite active galactic nuclei (AGN) activity and star formation. In this work, we analyze [C ii ]158 μ m and continuum observations from the Atacama Large Millimeter/submillimeter Array for a sample of four radio AGN at z  ≈ 3.5, focusing on eight associated companion cloud systems discovered within projected distances of tens of kiloparsecs or less. The spatial distribution of these companions indicates that the majority of cold gas is not located at the AGN position, i.e., not in their host galaxies. With the assistance of [C ii ] at 0 $\mathop{.}\limits^{\unicode{x02033}}$ 2 resolution, we further confirm the gas-poor nature of the hosts by reanalyzing archival [C i ] (a tracer of H _2 ) at ∼2″ resolution. Our sample has [C ii ] luminosities in a range of 2.8 × 10 ^8  <  L _[C II] / L _⊙  < 4.2 × 10 ^9 . The L _[C II] / L _IR ratio, ∼9.4 × 10 ^−4 , is consistent with sources discussed in the literature. Our findings show the gas-poor radio AGN hosts have nearby gas-rich companions. We propose that these companions may be stripped clouds resulting from merger processes, which could be a trigger of radio-loud AGN. They may also be a signature of negative AGN feedback (e.g., shock heating) on these infalling companions and on the host galaxy. In general, our analysis shows that powerful AGN at and before Cosmic Noon are impacting and being impacted by cold gaseous clouds in their circumgalactic or protointracluster media.